Wiarygodność polityki pieniężnej w krajach stosujących strategię bezpośredniego celu inflacyjnego - Kurach, Radosław; Stelmach, Jerzy (Monetary Policy Credibility in the Inflation Targeting Countries, 2007)
Monetary policy credibility in the inflation targeting strategy may be defined as the difference between inflation target and the publics' inflation expectations. The objective of this paper is to evaluate monetary policy credibility of some inflation targeting countries by analyzing the inflation expectations formation of consumers and commercial bank analysts. We examine three countries that have adopted IT strategy - The Czech Republic, New Zealand, and Poland. Matching the empirical results we make the recommendation on using the method of evaluating monetary policy credibility.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 20-31